Layered GeI2: A wide-bandgap semiconductor for thermoelectric applications–A perspective - Dhingra, Archit (Frontiers in Nanotechnology, 2022)
Layered GeI2 is a two-dimensional wide-bandgap van der Waals semiconductor, which is theorized to be a promising material for thermoelectric applications. While the value of the experimentally extrapolated indirect optical bandgap of GeI2 is found to be consistent with the existing theoretical calculations, its potential as a thermoelectric material still lacks experimental validation. In this Perspective, recent experimental efforts aimed towards investigating its dynamical properties and tuning its bandgap further, via intercalation, are discussed. A thorough understanding of its dynamical properties elucidates the extent of electron-phonon scattering in this system, knowledge of which is crucial in order to open pathways for future studies aiming to realize GeI2-based thermoelectric devices.